Choosing the Right Store: How Open-Ended Task Help Middle School Students Learn Financial Literacy - Sagita, Laela; Putri, Ratu Ilma Indra; Zulkardi; Prahmana, Rully Charitas Indra (Mathematics Education Journal, 2025)
This study explores how junior high school students understand different types of discounts through percent multiplication. We used the qualitative study and analyzed the in-depth answers of three of the 32 participants as research subjects. The end-of-year discount selection activity provides a daily context to build knowledge about needs and wants. Students engage with open-ended tasks requiring mathematical methods to make financial decisions. These activities help students recognize discounts in everyday life, develop problem-solving strategies, and improve mathematical skills. The article highlights how students analyze various store discounts and guide readers in distinguishing between needs and wants. Early exposure to financial math fosters responsible consumer behavior. The study emphasizes the importance of applying comprehensive information to solve financial problems by connecting mathematics to real-life scenarios. The results indicate that the implementation of an open-ended task has the potential to facilitate understanding of financial decision-making and mathematical skills.